Conservative vs radical bowel surgery for endometriosis: A systematic analysis of complications. - Heinz‐Partington, Sean; Costa, Walter; Martins, Wellington P.; Condous, George (Australian & New Zealand Journal of Obstetrics & Gynaecology, 2021)
Background: Endometriosis of the bowel can be associated with significant morbidity. Surgery to remove it carries risks. Options include conservative shaving or discoid resection and more radical segmental bowel resection. Aims: To determine if more conservative shaving or discoid bowel resection is associated with fewer risks than more radical segmental resection. Material and Methods: This study is a systematic review. We considered eligible any cohort, observational or randomised controlled trial (RCT) study of at least ten women per arm comparing conservative vs radical bowel surgery for endometriosis. We divided complications into two groups, major and minor. One additional article was added due to its significance in answering our study question as well as the high quality of the study design as an RCT. Results: There were 3041 studies screened. Eleven studies were included (n = 1648). For major complications, the risk ratio for shaving and disc excision vs segmental resection is 0.31 (95% CI 0.21–0.46), while the risk difference is −0.25 (95% CI −0.41 to 0.10). For minor complications, the risk ratio is 0.63 (95% CI 0.36–1.09), while the risk difference is −0.03 (95% CI −0.12 to 0.05). Conclusions: Conservative shaving or discoid excision surgery is associated with reduced complications. Previous studies demonstrated a trend toward this finding, but suffered from relatively low participant numbers, increasing the risk of type one statistical error. Our results allow surgeons to make informed choices about potential complications when deciding how to approach bowel endometriosis. The results also allow patients to have more information about the risks. However, outcomes in the studies analysed are heterogenous and are from low‐quality evidence.